2014
DOI: 10.1186/s12052-014-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-lab learning activities, a post-lab written report, and content reduction on evolution-based learning in an undergraduate plant biodiversity lab

Abstract: Background: Commonplace biodiversity labs in introductory undergraduate biology typically emphasize declarative knowledge. We contend that shifting these labs to emphasize evolution, higher-order cognition, and science reasoning would benefit student learning. Four factors that likely make evolution-based higher-order learning goals difficult to achieve in these labs are: the novelty and quantity of required declarative knowledge, the number of integrated concepts, the theoretical nature of evolution, and limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Prior research indicates that courses with hands-on activities, such as labs, increase enthusiasm and learning in students (Basey et al, 2014). Therefore, our course was designed to focus on lab activities, with discussion-based lectures serving to introduce core content that was later incorporated into laboratory material.…”
Section: Course Development and Methodsmentioning
confidence: 99%
“…Prior research indicates that courses with hands-on activities, such as labs, increase enthusiasm and learning in students (Basey et al, 2014). Therefore, our course was designed to focus on lab activities, with discussion-based lectures serving to introduce core content that was later incorporated into laboratory material.…”
Section: Course Development and Methodsmentioning
confidence: 99%
“…Both lab styles had a 3-wk preparatory lab experience, a hands-on focal lab experience, and a postlab write-up. In a concurrent study, Basey et al . (2014) demonstrated that both lab styles examined in this study significantly improved student learning of lecture-specific material at both the LO declarative knowledge level and evolution-based HO integration level with a margin of improvement ranging from 6.3 to 11%.…”
Section: Research Goalsmentioning
confidence: 98%
“…Why do commonplace biodiversity labs take on a “march through the phyla” approach and emphasize declarative knowledge? Basey et al . (2014) contended that the shift from an emphasis on declarative knowledge to evolution-based HO learning in biodiversity labs is difficult to successfully achieve because of the potential for cognitive overload due to three interacting factors: the high quantity and novelty of required foundational declarative knowledge, the extensive interactivity of concepts, and the theoretical nature of evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Since the lab is the main part of the course, it should be emphasized through pre- and post- lab elements (Figure 4) in order to improve student conceptual understanding of extended surfaces as well as scientific reasoning . 12, 13 In the pre-lab part, students receive the lab handout which gives detailed instructions on experimental procedure. Students work in small groups (3-4 students), organizing and sharing tasks.…”
Section: Example Of Extended Surfaces Laboratory Application In Under...mentioning
confidence: 99%